2014
DOI: 10.3390/molecules190914979
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Effects of “Jutsu” (Atractylodis rhizome and Atractylodis lanceae rhizome) on 1-(2,5-Dimethoxy-4-iodophenyl)-2-aminopropane (DOI)-Induced Head Twitch Response in Mice (I)

Abstract: Abstract:Hallucinations are a common non-motor symptom of Parkinson's disease and various forms of dementias. Yokukansan and Yokukansankachimpihange have attracted attention due to their effectiveness in the treatment of hallucinations of dementia. To clarify which component in these formulas contribute to the effects, at first, we focused on their differences in compositions to examine the pharmacological effects on the selective 5-HT2A/2C agonist 1-(2,5-dimethoxy-4-iodophenyl)-2-aminopropane (DOI)-induced he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
(14 reference statements)
0
9
0
Order By: Relevance
“…The pharmacological activity of the AR on the central nervous system has been demonstrated in various animal models with regards to its effects on the general behavior and spontaneous movement, potentiation of hypnotic action of hexobarbital sodium, and anti-electroshock convulsion. Murayama et al (2014) indicated that water extract of A. japonica showed a stronger inhibitory effect on 1-(2, 5-dimethoxy-4-iodophenyl)-2-aminopropane (DOI)-induced head-twitch response than that of A. lancea corresponding to their major constituents of atractylenolide III and β-eudesmol, and suggested that the major constituents should be active constituents contributing to the antihallucination effects of Byaku- and So-jutsu. Besides, the part B–C ring (butenolide) in ATL III was found to be similar to the structure of serotonin and suggested that the B–C ring may partially play role in antagonistic activity against serotonin receptors.…”
Section: Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation
“…The pharmacological activity of the AR on the central nervous system has been demonstrated in various animal models with regards to its effects on the general behavior and spontaneous movement, potentiation of hypnotic action of hexobarbital sodium, and anti-electroshock convulsion. Murayama et al (2014) indicated that water extract of A. japonica showed a stronger inhibitory effect on 1-(2, 5-dimethoxy-4-iodophenyl)-2-aminopropane (DOI)-induced head-twitch response than that of A. lancea corresponding to their major constituents of atractylenolide III and β-eudesmol, and suggested that the major constituents should be active constituents contributing to the antihallucination effects of Byaku- and So-jutsu. Besides, the part B–C ring (butenolide) in ATL III was found to be similar to the structure of serotonin and suggested that the B–C ring may partially play role in antagonistic activity against serotonin receptors.…”
Section: Pharmacologymentioning
confidence: 99%
“…Besides, the part B–C ring (butenolide) in ATL III was found to be similar to the structure of serotonin and suggested that the B–C ring may partially play role in antagonistic activity against serotonin receptors. Thus, a rational design of butenolide-related compounds may produce potential lead compounds for new drug development ( Murayama et al, 2014 ). ATL-III presented a neuroprotective effect on learning and memory impairment rats by decreasing ROS production and protein kinase C level ( Zhao et al, 2015 ).…”
Section: Pharmacologymentioning
confidence: 99%
“…The ethanol extract of AL exerted an essential inhibitory effect on lipase with the IC 50 9.06 µg/mL in a human pancreatic lipase assay, and exhibited anti-obesity effect on a high-fat diet-induced obesity mice model at the high concentration of 500 mg/kg [ 14 ]. The water extracts from AL showed the antagonistic activity against serotonin receptors and an inhibitory effect on the selective 5-HT2A/2C agonist 1-(2,5-dimethoxy-4-iodophenyl)-2-aminopropane-induced head-twitch response in mice [ 15 ]. Water extracts from AL reduced triptolide-induced toxicity through the down-regulation of the hepatic expression of CYP3A.…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…Furthermore, YKSCH treatment prolongs the total sleeping time and tends to increase sleep efficacy based on polysomnography recordings in normal young healthy subjects (3). YKSCH treatment has also been reported to reduce memory impairment and BPSD-like behavior, such as hallucinations and aggressive behavior, in several rodent models (4)(5)(6)(7). Although some research using animal models have begun to elucidate the action of YKSCH in the central nervous system, little is known about how YKSCH alleviates insomnia observed in clinical practice.…”
Section: Introductionmentioning
confidence: 99%